Identifikasi dan model ruang terbuka hijau sebagai ruang evakuasi bencana alam gempa bumi berbasis SIG di kawasan Sanur, Denpasar, Bali - Rashifah, Nadiyah; Lanya, Indayati; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
Identification and model on green open space as evacuation area of earthquake at Sanur, South Denpasar, Bali. Bali Island is one of Indonesia's seismotectonics as it is passed through the Mediterranean mountain range and the subduction zone between the Eurasian Plate and the Indo-Australian Plate. The southern area of Bali is vulnerable to earthquake and one of the most vulnerable to the earthquake is Sanur. Sanur area has an area of 10,57 km² or 1.057 hectares with a population of 28.527 inhabitants. Therefore, earthquake mitigation such as physical mitigation is to utilize green open space as an evacuation area is considered to be important. The purpose of this research is to identify the suitability of green open space as an evacuation area and to determine the green evacuation open space concept model. This research used satellite image interpretation and field survey methode. The data used is data of the earthquake center point throughout in Sanur along with potential tsunami risk map, green open space map and accessibility map. The parameters used were green open space width of at least 500 m², types of green open space, accessibility, and potential earthquake and tsunami. Result showed that the green open space which suitable as an evacuation area was about 292 hectar and not suitable is 93 hectar. Furtheremore, the suitable green open space evacuation map was generated into two evacuation space concept. There were micro evacuation space and macro evacuation space. The micro evacuation space focuses on individual rescue while the macro evacuation space focuses on mass rescue.